Pemanfaatan Sistem Infromasi Geografis Berbasis Internet Sebagai Media Pembelajaran Jarak Jauh - Sejati, Sadewa Purba; Sekarsih, Fitria Nuraini; Nucifera, Fitria; Permatasari, Afrinia Lidistya (Universitas Muhammadiyah Mataram, 2025)
Abstract: Implementing distance learning as a new form of habit during the COVID-19 pandemic has raised several problems. The transition from conventional learning methods to distance learning has quickly resulted in learning media not being fully prepared. This problem can result in a lack of understanding of the subject matter of the learning material among students. The dynamics of learning issues during the pandemic allow the author to introduce internet-based GIS as a distance learning medium for students majoring in forestry at SMK Widya Nusantara Maros. The activity aims to introduce the geographic information system (internet-based GIS) as a learning medium for vocational high school students. The method of the activity is training. The activity is divided into three stages, namely the preparation stage, the implementation stage, and the evaluation stage. ArcGIS Online was chosen as a distance learning medium. The activity results show that internet-based GIS can be used as an alternative to achieve learning outcomes in distance learning.Abstrak: Penerapan pembelajaran jarak jauh sebagai bentuk kebiasaan baru saat pandemi Covid-19 menimbulkan beberapa persoalan. Transisi metode pembelajaran konvensional menjadi pembelajaran jarak jauh dalam waktu singkat mengakibatkan media pembelajaran belum sepenuhnya disiapkan dengan baik. Persoalan ini berpotensi mengakibatkan kurangnya pemahaman siswa terhadap pokok materi pembelajaran. Dinamika persoalan pembelajaran saat pandemi memberikan ruang bagi penulis untuk mengenalkan SIG berbasis internet sebagai media pembelajaran jarak jauh siswa jurusan kehutanan di SMK Widya Nusantara Maros. Tujuan kegiatan adalah mengenalkan sistem informasi geografis (SIG berbasis internet sebagai media pembelajaran bagi siswa-siswi sekolah menengah kejuruan. Metode kegiatan adalah pelatihan. Kegiatan dibagi menjadi tiga tahap, yaitu tahap persiapan, tahap pelaksanaan, dan tahap evaluasi. Arc GIS online dipilih sebagai media pembelajaran jarak jauh. Hasil kegiatan menunjukkan bahwa SIG berbasis internet mampu digunakan sebagai alternatif untuk mencapai capaian pembelajaran dalam pembelajaran jarak jauh.